Difference in the duration of pediatric diabetic ketoacidosis: Comparison of new-onset to known type 1 diabetes (2020)
Objective: To compare the duration (hours until (Formula presented.) ? 15 mmol/L) of diabetic ketoacidosis (DKA) episodes that are the first manifestation of new type 1 diabetes (NT1D) and those that are a complication in patients with previously diagnosed type 1 diabetes (PT1D). Methods: A multicenter retrospective cohort study was designed. The duration of DKA was measured from the start of the treatment. The primary outcome was the comparison of the time needed in each group to reach (Formula presented.) ? 15 mmol/L. The secondary outcomes were the comparison of the time to reach pH ? 7.3 and length of hospital stay in each group. Data were analyzed with a bivariate analysis of the variables vs primary outcome. Then, a regression model was analyzed. Results There were 305 episodes included (NT1D: 115, PT1D: 190). DKA in the NT1D group lasted longer (NT1D 20 (16-19) vs PT1D 12 (8-16), hours, P less than .01) with a significant difference in each level of DKA severity. This group also took longer to reach pH ? 7.3 (NT1D 16 (12-22) vs PT1D 9 (6-12), hours, P less than .01) and had a longer hospital stay (NT1D 9 (6-12) vs PT1D 7 (4-10), hours, P less than .01). Conclusion: The duration of DKA is longer in patients with NT1D regardless of characteristics like DKA severity, duration of symptoms, and type of treatments received. © 2020 John Wiley and Sons A/S. Published by John Wiley and Sons Ltd